Lime and gypsum management regimes: short term soil chemical properties alterations and initial maize growth - Gomes, Laura Carolina CollaÃ§o; Quartucci, Felipe (REVISTA DE AGRICULTURA, 2021)
The objective of this work was to evaluate the short-term chemical changes in the soil and the initial maize growth as a function of different lime and gypsum management regimes. An experiment was set up in PVC tubes and the effects were evaluated at depths of 0-15cm and 15-30cm after 2 months. A second experiment was carried out in pots where maize was planted, and aerial and root system development were evaluated. The use of limestone and gypsum was tested separately, applied both at the same time and spaced one month apart, plus a control treatment. The application of limestone and gypsum at the same time and only limestone were the treatments that caused the most changes in the soil in the 0-15cm layer after 2 months. The combination of limestone and gypsum also increased root growth and therefore may be an interesting strategy for short-term soil correction.